Model Tests and Numerical Simulations of Liquefaction and Lateral Spreading II LEAP-ASIA-2019 - Tobita, Tetsuo; Ichii, Koji.; Ueda, Kyohei; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This open access book presents work collected through the Liquefaction Experiments and Analysis Projects (LEAP) in 2019 (LEAP-ASIA-2019) following the LEAP-UCD-2017 whose results have been published as a first volume. In addition to the research targets set in the previous one, such as the repeatability, variability, and sensitivity of lateral spreading on mildly sloping liquefiable sand, this volume includes research efforts to validate the generalized scaling law (hereafter (3z(BGSL(3y(B) for the identical prototype with the one employed in UCD-2017. In LEAP-ASIA-2019, 10 institutes around the world conducted 23 tests in total. It was the first multi-institutional attempts to investigate the validity of the generalized scaling law for the saturated sandy sloping deposit with wide range of initial conditions. The experimental data provided a unique basis for assessing the capabilities of six different simulation platforms for numerical simulation of soil liquefaction. The results of the experiments and the numerical simulations are presented and discussed in papers submitted by the project participants.s
Part 1. Overview Papers -- 1. Summary of centrifuge experiments on liquefaction-induced lateral spreading: Validation and applicability of the generalized scaling law -- 2. LEAP-ASIA-2019 Simulation Exercise: Calibration of Constitutive Models and Simulations of the Element Tests -- 3. LEAP-ASIA-2019 Simulation Exercise: Comparison of the Type-B and Type-C Numerical Simulations with Centrifuge Test Results -- 4. Dynamic Torsional Shear Tests of Ottawa F-65 Sand for LEAP-ASIA-2019 -- Part 2. Centrifuge Experiment Papers -- 5. LEAP-ASIA-2019 Centrifuge Tests at University of Cambridge -- 6. LEAP-ASIA-2019 Centrifuge Test at University of California, Davis -- 7. LEAP-ASIA-2019 Centrifuge Test at Ehime University -- 8. LEAP-ASIA-2019 Centrifuge Tests at University Gustave Eiffel -- 9. LEAP-ASIA-2019 Centrifuge Test at KAIST -- 10. LEAP-ASIA-2019 Centrifuge Test at Kyoto University -- 11. LEAP-ASIA-2019 Centrifuge Test at NCU -- 12. Experimental Evaluation of Lateral Spreading of a Liquefiable Sloping Deposit Using Centrifuge and Generalized Scaling Law Tests -- 13. Centrifuge Model Tests at Zhejiang University for LEAP-ASIA-2019 -- Part 3. Numerical Simulation Papers -- 14. Type-C Simulations of Centrifuge Tests from LEAP-ASIA-2019 using SANISAND-Sf -- 15. LEAP-ASIA-2019 Type-B Simulations through Strain Space Multiple Mechanism Model -- 16. LEAP-ASIA-2019 Centrifuge Test Simulation at UNINA -- 17. LEAP-ASIA-2019 Centrifuge Test Simulations of Liquefiable Sloping Ground -- 18. LEAP-ASIA-2019 Type-B Simulations through FLIP at Kyoto University -- 19. LEAP-ASIA-2019 Simulations at Tsinghua University -- 20. Class-C simulations of LEAP ASIA-2019 via OpenSees platform by using a pressure dependent multi yield-surface model.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Engineering geology; Geotechnical engineering; Computer simulation; Rock mechanics; Soil mechanics; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Computer Modelling; Soil and Rock Mechanics